Investigating document triage on paper and electronic media - Buchanan, George R.; Loizides, Fernando (My University, 2007)
Document triage is the critical point in the information seeking process when the user first decides the relevance of a document to their information need. This complex process is not yet well understood, and subsequently we have undertaken a comparison of this task in both electronic and paper media. The results reveal that in each medium human judgement is influenced by different factors, and confirm some unproven hypotheses. How users claim they perform triage, and what they actually do, are often not the same
Keywords: User interfaces (Computer science); Computer science--Digital libraries; Information behavior